Evidence for the Effectiveness of Remdesivir (GS-5734), a Nucleoside-Analog Antiviral Drug in the Inhibition of IK(M) or IK(DR) and in the Stimulation of IMEP - Chang, Wei-Ting; Liu, Ping-Yen; Gao, Zi-Han; Lee, Shih-Wei; Lee, Wen-Kai; Wu, Sheng-Nan (Frontiers in Pharmacology, 2020)
Remdesivir (RDV, GS-5734), a broad-spectrum antiviral drug in the class of nucleotide analogs, has been tailored for treatment of coronavirus infections. However, whether this compound produces any effects on different types of membrane ion currents remains unresolved. The possible perturbations of RDV on ionic currents in pituitary GH3 cells and Jurkat T-lymphocytes were investigated in this study. The whole-cell current recordings demonstrated that RDV effectively and differentially depressed the peak or late components of IK(DR) elicited by membrane depolarization in GH3 cells with effective IC50 values of 10.1 or 2.8 M, respectively; while, the value of dissociation constant for RDV-mediated block of IK(DR) was 3.04 M. The steady-state inactivation of IK(DR) in the presence of RDV was constructed, and recovery from IK(DR) block was slowed. RDV-induced block of IK(DR) was not reversed by either ,-methylene ATP or cyclopentyl-1,3-dipropylxanthine. The RDV addition also depressed the amplitude of M-type K+ current with an IC50 value of 2.5 M. The magnitude of voltage hysteresis of IK(M) elicited by long-lasting triangular ramp pulse was decreased by adding RDV. Membrane electroporation-induced current in response to large membrane hyperpolarization was enhanced, with an EC50 value of 5.8 M. Likewise, in Jurkat T-lymphocytes, the addition of RDV suppressed IK(DR) amplitude in combination with the increased rate of current inactivation applied by step depolarization. Collectively, RDV appears to be a prodrug and its inhibition of IK(DR) and IK(M) and stimulation of IMEP occurring in a non-genomic fashion might provide additional mechanisms through which cellular functions are seriously perturbed.